Quantifying bias and inaccuracy of upper-level aggregation in HICPs for Germany and the euro area - Julika Herzberg; Thomas A. Knetsch; Patrick Schwind; Sebastian Weinand (Deutsche Bundesbank, 2021)
Current HICP measurement practices produce an upward bias of about one-ninth of a percentage point in German inflation due to changing consumption being disregarded and the preliminary data being used in the compilation of expenditure weights. The statistical uncertainty produced by these sources of mismeasurement can be illustrated by an interdecile range of about one-quarter of a percentage point. The annual updating of the quantity component of the weights, which was implemented in 2012, has reduced the substitution component, making the disregard of changing consumption virtually a non-issue for the euro area HICP. The measurement of the German HICP is impaired by the extrapolation of expenditure weights, and the use of preliminary national accounts data since 2012 has not led to an improvement. This source of mismeasurement is likely to be relevant for the euro area HICP as well but cannot be quantified due to data constraints. Compilers might identify weight updating techniques as a potential field of HICP quality improvement. For the time being, users have to consider this source of mismeasurement when assessing the precision of the HICP as a measure of "true" inflation.
Keywords: E31; C43; 330; Inflation measurement; Substitution bias; Updating of expenditure weights; HICP